2014
DOI: 10.1186/1471-2482-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences between age groups regarding colorectal surgery in elderly patients?

Abstract: BackgroundSurgical procedures with curative or palliative intentions in subjects aged over 70 represent a colorectal surgical challenge due to the issue they raise: Benefits versus increased morbidity. In this study, we proposed to compare the impact of surgery with the surgical intervention short-term results and analyze the factors that may influence these results in elderly age groups.MethodsWe retrospectively analyzed a database containing information about patients who underwent colorectal surgery from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
1
24
1
Order By: Relevance
“…Elderly is a very subjective term based mainly on the environmental culture of the patient. Elderly has been defined as a chronological age of ≥65 years of age, which has been further subdivided into early and late elderly for those who are 65 through 74 and over 75 years of age, respectively [ 8 ]. To the best of our knowledge, this is the first study about the outcome of colorectal surgery in elderly patients with comparison to a cohort group of nonelderly patients manually matched for BMI, ASA score, CCI and procedure performed (open vs. laparoscopic, elective vs. urgent).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly is a very subjective term based mainly on the environmental culture of the patient. Elderly has been defined as a chronological age of ≥65 years of age, which has been further subdivided into early and late elderly for those who are 65 through 74 and over 75 years of age, respectively [ 8 ]. To the best of our knowledge, this is the first study about the outcome of colorectal surgery in elderly patients with comparison to a cohort group of nonelderly patients manually matched for BMI, ASA score, CCI and procedure performed (open vs. laparoscopic, elective vs. urgent).…”
Section: Discussionmentioning
confidence: 99%
“…Tolerability of surgery by elderly patients aged ≥ 80 years has been investigated in several studies and showed favorable outcomes in terms of postoperative mortality as compared with that of younger patients [11][12][13]. When "elderly" was defined as ≥ 75 years, the cancer-specific survival rate of elderly CRC patients receiving surgical treatment was not significantly different from that of younger patients [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bircan et al evaluated the impact of colorectal surgery on the short-term results and analyzed the factors that had the potential to influence these results in elderly patients, in a study conducted between January 2008 and December 2013. A total of 265 patients were enrolled and analyzed in that retrospective study (6). Among the patients who underwent surgery during the study period, 110 were between 60 and 69 years of age (group 1), 99 were between 70 and 79 years of age and 56 were ≥80 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have excluded patients in this age group. Furthermore, few authors have evaluated the short-and long-term outcomes of colorectomy for colorectal adenocarcinoma patients of ≥80 years of age (5,6). Thus, the short-term outcomes and long-term survival of elderly patients who undergo colorectomy for colorectal adenocarcinoma remain unclear.…”
Section: Introductionmentioning
confidence: 99%